EVEKTIFITAS PEMANFAATAN RUANG TERBUKA PUBLIK DI TAMAN SULTAN HASANUDDIN GOWA - Rahayu, Irma; Jaharuddin, Wahyuni Ayu (Teknosains: Media Informasi Sains dan Teknologi, 2020)
The importance of the existence of Green Open Space (RTH) in urban areas has begun to be felt by the community at this time. By looking at the phenomenon of the many public open spaces that are changing their faces into new high-rise buildings and housing, it has encouraged the enthusiasm of some people to restore the role of public space in urban areas. Various environmentalists took part, including the government through the Ministry of Public Works and Public Housing, various communities including the implementers of the 2015 world habitat day activity (HHD2015) and writers, to voice the urgency of public space and share ideas and strategies for encourage the realization of public space for all communities. Sultan Hasanuddin Park is a park located in Gowa Regency, but it is not passed by public transportation. Sultan Hasanuddin Park also has several supporting facilities but it does not function properly and some have been damaged. This study uses a qualitative descriptive method, which describes a phenomenon, events and conditions that exist. This study aims to Analyze the pattern of spatial use in Sultan Hasanuddin Park, Identify factors influencing the effectiveness of the utilization of the Sultan Hasanuddin Makassar Park facility and Analyze the utilization of supporting facilities for Sultan Hasanuddin Park as a public open space. The results showed that the Sultan Hasanuddin Park did not function properly, due to the lack of shade in the seating area, so that the upholders sat in a shaded area and not in the proper seat. The absence of a clear parking area so that the end of the park in the park and the absence of public bins so that one corner of the park used as public TPU. Lack of care / janitors who take care of the park so that plants and grasses that exist in the garden are not maintained.